Sir G. (London : Male Classics.)
Fonds Suzan Daniel (FSD)
Verschijnt vanaf n° 12 als 'Sir Gee'
F/02/016 Archief Roger Vertongen
Periodiciteit : tweemaandelijks
Redactie : Male Classics, 15 Kensington High Street, London, W8
Engels
Periodiek